Antibiofilm and antibacterial activity of maslinic acid against Vancomycin-Resistant Enterococci (VRE) - Somaia M. Abdelmegeed; Mohamed F. Mohamed; Mohamed N. Seleem (PLoS ONE, 2026)
The emergence of vancomycin-resistant Enterococcus (VRE) has posed a significant global health threat, especially in healthcare settings where treatment options are increasingly limited due to rising antibiotic resistance. Maslinic acid, a naturally occurring pentacyclic triterpene found in olives, is known for its diverse biological activities, including anti-inflammatory, anticancer, antioxidant, and antimicrobial effects. In this study, we investigated the antibacterial and antibiofilm potential of maslinic acid against VRE. Initial screening identified maslinic acid as a potent hit, with minimum inhibitory concentrations (MICs) ranging from 4 to 8 µg/mL across 13 clinical enterococcal isolates, including multidrug-resistant strains. Time-kill assays demonstrated bacteriostatic activity comparable to linezolid, while cytotoxicity and hemolysis assays confirmed its safety in mammalian cells. Furthermore, maslinic acid disrupted established Enterococcus faecalis biofilms by approximately 50%, whereas linezolid was not effective against biofilms. Notably, maslinic acid significantly reduced bacterial burden in a Caenorhabditis elegans infection model by 80%, outperforming linezolid. These findings highlight maslinic acid as a promising candidate for the development of new therapies targeting VRE, with the added advantage of antibiofilm activity and a favorable safety profile.